1994
DOI: 10.1038/bjc.1994.432
|View full text |Cite
|
Sign up to set email alerts
|

Registration quality and descriptive epidemiology of childhood brain tumours in Scotland 1975-90

Abstract: S_nary Children (0-14 years) with malignant brain and central nervous system (CNS) tumours (ICD9 191 and 192) were listed from the Scottish Cancer Registration Scheme for the years 1975-90. These cases formed the basis for validation and verification procedures aimed at providing a complete and accurate data set for epidemiological analyses. A variety of data sources were cross-checked to optimise ascertainment, and resulting from this 5.7% of validated cases were found on the cancer registry with diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
28
4

Year Published

1995
1995
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 13 publications
2
28
4
Order By: Relevance
“…Overall, these findings agree with those of most previous studies (Blair and Birch, 1994;McKinney et al, 1994;Bunin et al, 1996;Gurney et al, 1996;Hjalmars et al, 1999;McNally et al, 2001;Dreifaldt et al, 2004), although differences have been found. Thus, a British study showed a stable rate of ependymomas (McNally et al, 2001), one study in the USA showed a stable rate of primitive neuroectodermal tumours (Gurney et al, 1996) and another study in the USA, spanning 21 years, showed that increases in the incidence rates of various morphological subgroups depends on the period studied .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Overall, these findings agree with those of most previous studies (Blair and Birch, 1994;McKinney et al, 1994;Bunin et al, 1996;Gurney et al, 1996;Hjalmars et al, 1999;McNally et al, 2001;Dreifaldt et al, 2004), although differences have been found. Thus, a British study showed a stable rate of ependymomas (McNally et al, 2001), one study in the USA showed a stable rate of primitive neuroectodermal tumours (Gurney et al, 1996) and another study in the USA, spanning 21 years, showed that increases in the incidence rates of various morphological subgroups depends on the period studied .…”
Section: Discussionsupporting
confidence: 92%
“…Cases were identified from a nationwide, clinical CNS tumour database and two independent population-based registers, both of which benefit from mandatory registration, resulting in virtually complete case ascertainment. In addition, use of medical records, including reports on pathology and neuroimaging, ensured better validity of the diagnoses than cancer registry data alone (McKinney et al, 1994;Thorsteinsson et al, 2005). Furthermore, the same persons coded all the tumours according to the ICD-O to ensure consistent coding practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The oxerall incidence of CNS tumours in York-shire (28.0 per million) is similar to that previouslI reported for Britain (27.0) and Scotland (29.0) (McKinnev et al 1994 (Miltenburg et al 1996) and 36 and 31 for boys and girls respectixely in the USA (Dexesa et al 1995).…”
Section: Discussionsupporting
confidence: 75%